Line managers and employees use of lean task boards in Norwegian municipal healthcare sector: a tool for action learning?. Issue 4 (16th October 2020) - Antonsen, Yngve; Bye, Geir
Abstract : Purpose: This study aims to analyse the line managers and employees' use of lean task boards over time in Norwegian municipalities using action learning theory. The research question was the following: what kind of action learning processes do the line managers and employees' use of the lean task board promote in municipalities' healthcare units? Design/methodology/approach: This qualitative case study data from a Norwegian municipality involved analyses of 750 internal self-recorded logs from task board sessions from 6 different units and 25 semi-structured interviews of managers and employees. Findings: The task board works for line managers to make employees responsible for forwarding ideas, solutions and implementation of new actions. The use of the task boards contributes to systemising work through establishing new routines and improving orderliness at work. The line managers used the task boards as a project management system to track progress in the purchasing of diverse equipment and initiatives to improve professionalism and their units' facilities. The study explains the learning challenges for managers using the lean task board, as the method promotes finding experience-based solutions that do not involve critical reflection and use of theory. Practical implications: The lean task board is well-suited for managers to promote learning processes that counteract chaos in local healthcare organisations. However, the task board has limitations as a method for improving services amongst healthcare units and for solving difficult problems. Originality/value: The study contributes to understanding how action learning theory can be applied to the analysis of the results of lean task board sessions